Sixty-seven years of the Nash program: Time for retirement? - Roberto Serrano (SERIEs - Journal of the Spanish Economic Association, 2021)
The Nash program is an important research agenda initiated in Nash (Econometrica 21:128-140, 1953) in order to bridge the gap between the noncooperative and cooperative counterparts of game theory. The program is thus turning sixty-seven years old, but I will argue it is not ready for retirement, as it is full of energy and one can still propose important directions to be explored. This paper completes and updates previous surveys, and suggests several directions for future research.
Keywords: C71; C72; C78; 330; Nash program; Bargaining; Implementation